ЗБЕРЕЖЕННЯ БЕТАНІНУ ПІД ЧАС СУШІННЯ СТОЛОВОГО БУРЯКА - Petrova, Z. (Institute of Engineering Thermophysics of NAS of Ukraine, 2023)
The effect of pretreatment of red beetroot at the stage of preparation for drying on physicochemical properties was investigated. An energy-efficient method of preparing antioxidant raw materials before drying with a complete replacement of heat treatment by blending was developed. This method of preparing beta-containing raw materials made it possible to preserve betanin by 95% and reduce the loss of energy carriers during the preparation of raw materials by 85 %.